The Social, Economic, And Political Foundations Of The Emergence Of Management Systems And Early States (Global Scientific Review, 2025)
This article provides information on the social, economic, and political foundations for the emergence of early states and the formation of governance systems in the territory of ancient Uzbekistan. It also discusses how initial views on the origin of the state emerged starting from the ancient and medieval periods, leading to the development of various theories. Proponents of these theories attempted to prove their respective viewpoints based on their ideologies, approaches, and worldviews. These theories predominantly feature abstraction and general philosophical methods, with less emphasis on the historical and legal aspects of the problem. Information is provided on the definitions given by scholars (R.V. Rtveladze, A.Kh. Saidov, A.V. Abdullayev) who have examined this issue, regarding a number of theories